TRADITIONAL CULTIVATION TECHNIQUES OF COCOA PLANTS AND THE UTILIZATION TURMERIC EXTRACT BECOME VEGETABLE PESTICIDES FOR MANAGING VASCULAR STREAK DIEBACK (VSD) - Munawir, Abdillah; Panggabean, Donwil; Bachtiar, Bachtiar; Muna, Siti Umamah Naili; Rusdiyanto, Edi; Nirmala, Sri Dewi (LPPM Univ. Ibn Khaldun Bogor, 2022)
The cocoa plant is the main ingredient in the manufacture of chocolate and its de-rivative products. The demand for cocoa derivative products is always high in line with the globalization of food and beverages made from chocolate. Traditional co-coa cultivation techniques are the main priority for farmers and the handling of Vascular Streak dieback (VSD) pests is a top priority for farmers. The purpose of this service is to improve the economy of cocoa farmers in Poli-Polia Village, Poli-Polia District, East Kolaka Regency. The method used is discussion, practice and demonstration material. The results of the shoot grafting technique for cacao seed-lings and the manufacture of organic fertilizers increase the productivity of cocoa plants and the results of turmeric extract can directly deal with VSD diseases that attack cocoa plants. In practice, the method of processing and the efficacy of tur-meric extract is the cause of not developing VSD disease in cocoa plants. On the other hand, cocoa yields can be sold at a high value based on training in harvesting techniques and how to improve the quality of cocoa beans.